Ultrafine grain formation and coating mechanism arising from a blast coating process: A transmission electron microscopy analysis. (11th October 2017) - Dunne, Conor F.; Roche, Kevin; Janssen, Arne; Zhong, Xiangli; Burke, M.G.; Twomey, Barry; Stanton, Kenneth T.
Abstract : This article examines the substrate/coating interface of a coating deposited onto mild steel and stainless steel substrates using an ambient temperature blast coating technique known as CoBlast. The process uses a coincident stream of an abrasive blast medium and coating medium particles to modify the substrate surface. The hypothesis for the high bond strength is that the abrasive medium roughens the surface while simultaneously disrupting the passivating oxide layer of the substrate, thereby exposing the reactive metal that then reacts with the coating medium. The aim of this study is to provide greater insight into the coating/substrate bonding mechanism by analysing the interface between a hydroxyapatite coating on both mild and stainless steel substrates. The coating adhesion was measured via a tensile test, and bond strengths of approximately 45 MPa were measured. The substrate/coating interface was examined using transmission electron microscopy and selected area diffraction. The analysis of the substrate/coating interface revealed the presence of ultrafine grains in both the coating and substrate at interface associated with deformation at the interface caused by particle impaction during deposition. The chemical reactivity resulting from the creation of these ultrafine grains is proposed to explain the high adhesive strength of CoBlast coatings.